The use of melatonin in the treatment of jet lag - clinical review - Karol Mazur; Dominik Machaj; Dominika Mazur; Aneta Asztabska; Alicja Płaczek (Kazimierz Wielki University, 2020)
Jet lag is a circadian rhythm disorder, that occurs as a result of air travel across multiple time zones. Jet lag symptoms include: anxiety, constipation, diarrhea, confusion, dehydration, headache, irritability, nausea, indigestion, difficulty concentrating, sweating, coordination problems, dizziness, daytime sleepiness, malaise, and memory loss. Melatonin, is a hormone that regulates the circadian rhythm by acting on MT1 and MT2 melatonin receptors. It is produced by pinealocytes in the pineal gland and released directly into the blood. Main therapeutical application of this medication is re-entraining disturbed circadian rhythms. All the mentioned studies proved that melatonin is effective in the treatment of jet lag. None of the mentioned above trials didn't report any serious side effects caused by this medication therefore occasional short-term use of melatonin seems to be safe. Most people should start treatment of jet lag with taking 2-3 mg melatonin, and if necessary increase the dose to 5 mg. Melatonin is the most effective in alleviating symptoms of jet lag when it is given at bedtime on the day of the flight and in the next few days after arrival. Further research is needed to find out the optimal dosage of melatonin fot treatment of jet lag, timing of its administration, time of initiation and duration of the treatment or possible side effects of this medication.